An overview of ground surface displacements generated by groundwater dynamics, revealed by InSAR techniques. (2017) - Radutu, A.; Nedelcu, I.; Gogu, C.R.
Abstract: One of the main activities causing subsidence in the urban environment is the dynamics of groundwater due to abstraction and recharge as well as its interaction with subsurface infrastructure systems. For a sustainable spatial planning, the complexity of urban environment demands the utilisation of new methods for monitoring and quantifying the effects of the underground processes. One of the remote sensing methods developed in the last decades, offering the opportunity for early detection of land subsidence in urban areas is the interferometric synthetic aperture radar (InSAR). By its different techniques, this method started to be used in correlation with several underground and ground measurements for revealing diverse parameters characterizing the dynamics of groundwater, including seasonal and long-term aquifer-system response. Considering both groundwater and underground structures, an overview of several studies realised in different sites, based on InSAR techniques, is presented.